G213 Handlebar Grip Related Injury Prevention (GRIP) feasibility study: Are exposed metal handlebar ends on children's bikes and scooters a risk factor for serious injury?. (27th April 2016) - Neilson, A; Hartshorn, S; Lyttle, M
Abstract : Aims: Handlebar-end impact is a well-recognised cause of major intra-abdominal injury in childhood. Through this feasibility study and the associated main study we aim to reduce the incidence and severity these injuries. Proper understanding of risk factors involved will help guide those responsible for setting safety standards. This feasibility study tested the research methodology proposed for the main study and collected data required to conduct power calculations for that study. Methods: In preparation for a multicentre case-control observational study we conducted a prospective feasibility study between March and September 2015 (REC approval 15/LO/0311). In the main study, handlebar end condition will be compared between children sustaining a handlebar-end injury [Cases] and riders whose injury did not involve the handlebar [Controls]. Children attending two UK tertiary paediatric hospitals with any bicycle or scooter injury were invited to participate in the feasibility study. Parents completed questionnaires regarding circumstances of the injury and condition of the handlebar ends, and clinical information regarding injuries was also collected. Postal and electronic reminders were used to complete datasets. Results: 522 families were invited to participate; 89 responses were received (17%). Response rates varied by method of approach: 27% (72/271) responded to invitations made in person while 6% (14/251) responded to postal invitations, and only 2% (3/146) responded to postal reminders. Following confirmation of eligibility and attempts to complete missing data, 38 Controls and 12 Cases were included. Eight Cases had serious abdominal injuries. Regarding the primary outcome of the proposed main study, exposed metal handlebar ends (see Figure 1 ) were more prevalent among Cases than Controls (odds ratio 2.5). Conclusion: This feasibility study will guide efficient design of the proposed multicentre case-control study. Information on recruitment rates may be generalizable to other studies. Only 10% of invitees provided eligible complete datasets. Invitation in person was the most effective recruitment method. An adequately powered, prospective study of handlebar grip condition within this injury mechanism is recommended.